Emergency and Supplemental Forages - Watson, Steve L.; Fjell, Dale L.; Fritz, John O.; Blasi, Dale A. (My University, 1993)
This publication describes emergency forages and how they should be used.
MF1073_1993-07
Keywords: MF1073; Crops; Livestock; MF